TANGGUNG JAWAB PERUSAHAAN ALIH DAYA TERHADAP PEKERJA OUTSOURCHING YANG TERKENA PEMUTUSAN HUBUNGAN KERJA DIMASA PANDEMI COVID-19 (STUDI DOKUMEN PERJANJIAN PENYEDIA JASA DI PT NTU) - Intan Mayasari Hutabarat; Martono Anggusti; Christina N.M Tobing (Nommensen Journal of Legal Opinion, 2021)
The Covid-19 pandemic has a very big impact in the industrial world, many companies have terminated employment (PHK) for workers, both PKWTT and PKWT. In the Manpower Act No. 13 of 2003 and the Job Creation Act No. 11 of 2020 concerning labor and termination of employment. Regarding termination of employment, termination of employment to outsourced workers, the author discusses 2 (two) problem formulations, namely: First: How is the responsibility of outsourcing companies to outsourcing workers / laborers who were terminated during the Covid-19 pandemic; Second, what is the comparison of the forms of legal protection for outsourcing workers / laborers who have experienced termination of employment according to Law no. 13 of 2003 concerning Manpower and Law no. 11 of 2020 About Job Creation. The research method used in this thesis is the Normative-Empirical method. The conclusion of this decision is First, that the outsourcing company is still in charge of the implementation of termination of employment, this can be seen in the PT SIS PKWT; Second, in terms of comparison between UUK No. 13 of 2003 with UUCK No.11 of 2020 not much has changed, only in UUKC regarding labor Outsourcing is more discussed.